2005
DOI: 10.1080/03601230500189246
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Behavior of Parathion in the Presence of Humic Acids from Different Origins

Abstract: This paper reports the effect of ultraviolet radiation on the degradation of pesticide ethyl parathion in the presence of humic acids. Ethyl parathion was completely degraded in 300 min using an artificial lamp of 7.41 x 10(-10) einstein/s. Humic acid from peat did not influence the photochemical rate (k = 8.92 x 10(-3) min). However, in the presence of aquatic humic acid, the photochemical rate was higher (11.5 x 10(-3) min). The analytical determinations show the presence of p-nitrophenol and aminophenol in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Several researchers have studied parathion photodegradation in different matrices, but their results significantly differed from each other with regard to reaction mechanisms and formation of byproducts (Grunwell and Erickson 1973; Mok et al, 1987; Sakellarides et al, 2003; Santos et al, 2005). The quantum yield at 254nm had been reported to be 6×10 −4 mol E −1 (Mok et al, 1987) while for a medium pressure lamp it was reported between 0.006 and 0.053 mol E −1 (Chen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have studied parathion photodegradation in different matrices, but their results significantly differed from each other with regard to reaction mechanisms and formation of byproducts (Grunwell and Erickson 1973; Mok et al, 1987; Sakellarides et al, 2003; Santos et al, 2005). The quantum yield at 254nm had been reported to be 6×10 −4 mol E −1 (Mok et al, 1987) while for a medium pressure lamp it was reported between 0.006 and 0.053 mol E −1 (Chen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 and H 2 O 2 were found to enhance the degradation of parathion. Controversial results regarding the role of humic substance in the photolysis of parathion were also reported by Sakellarides et al, (2003), who illustrated that humic substances significantly altered the degradation kinetics, while Santo et al, (2005), found humic substances had little effect on parathion photodegradation.…”
Section: Introductionmentioning
confidence: 99%